Cultural Mapping and the Sustainability of Coastalscapes: A Conceptual Approach - Daniel Oliveira; Zara Teixeira; Mônica Mesquita (European Journal of Geography)
Coastal regions, plentiful in ecological and economic value, have long been hubs for human settlement, recreation, and tourism. However, the growing threats of global climate change and urbanisation are endangering the sustainability of these vital coastalscapes. With nearly two-thirds of the global population living in coastal areas, there is an urgent need for innovative management strategies. This paper explores the critical role of local spatial knowledge, incorporating diverse cultural aspects such as memories, experiences, and oral traditions, to address the challenges confronting these regions. Cultural Mapping (CM) is introduced as a dynamic methodology – transcultural and transdisciplinary – facilitating creative representations of coastalscapes and serving as a vital tool for understanding the complex, reciprocal relationships between people, more-than-human entities, and places. CM reveals the deep-rooted connections that shape coastal communities’ identities and sustainability practices by documenting intangible cultural resources and capturing the emotional and sensory dimensions of coastal environments. Drawing on the pioneering work of Pam Hall (2013) and incorporating insights from an in-depth scholarly literature review, this paper underscores the potential of CM to transform both research practices and policymaking. It offers a new lens for sustainability in coastal regions, paving the way for future studies and innovative, community-driven management strategies that engage a diversity of knowledge systems in addressing pressing environmental challenges.